2017
DOI: 10.1097/wco.0000000000000453
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of progressive multiple sclerosis therapy

Abstract: Raising the profile of progressive MS has resulted in the first effective treatments with the promise of more to come.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…This is the first unequivocal confirmation that aluminium is increased in brain tissue in MS (Mold et al 2018b) and it further supports the contention that the body burden of aluminium is elevated in MS compared to individuals without MS (Exley et al 2006;Jones et al 2017). The data do not prove a role for aluminium in MS, but a higher content of a neurotoxin and powerful pro-oxidant (Verstraeten et al 1997;Exley 2004) in brain tissue in MS cannot be discarded as a putative aetiological factor in a disease with both genetic and environmental components (Thompson 2017). The results also have translational aspects in that they support previous research in which silicon-rich mineral waters were suggested as potential long-term therapies in treating MS (Jones et al 2017).…”
Section: Discussionsupporting
confidence: 65%
“…This is the first unequivocal confirmation that aluminium is increased in brain tissue in MS (Mold et al 2018b) and it further supports the contention that the body burden of aluminium is elevated in MS compared to individuals without MS (Exley et al 2006;Jones et al 2017). The data do not prove a role for aluminium in MS, but a higher content of a neurotoxin and powerful pro-oxidant (Verstraeten et al 1997;Exley 2004) in brain tissue in MS cannot be discarded as a putative aetiological factor in a disease with both genetic and environmental components (Thompson 2017). The results also have translational aspects in that they support previous research in which silicon-rich mineral waters were suggested as potential long-term therapies in treating MS (Jones et al 2017).…”
Section: Discussionsupporting
confidence: 65%
“…(2) The disease affects about 120,000 people in the United Kingdom (UK) with an incidence that appears to be increasing by approximately 2.5% per annum (4). There is a notably significant societal and global burden of £3bn/year (3) In order to comprehensively map the prevalence and characteristics of MS across the UK, the MS Society commissioned Swansea University Medical School, home to the Secure Anonymous Information Linkage (SAIL) Databank (4), to develop the UK Multiple Sclerosis Register (UKMSR). The SAIL databank is a safe haven for billions of person-based records combined with a complete data linkage and an analysis toolset.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some progress, advances in understanding the pathogenesis of MS remain frustratingly slow [1]. Effective treatments for MS are rare [2,3]. The consensus remains that MS is likely to involve both genetic and environmental factors acting either in isolation or together in various disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%